GAMBARAN MANAJEMEN DIRI MAHASISWA SAAT PANDEMI COVID-19 DITINJAU DARI JENIS KELAMIN - Rini Nurahaju (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT A Covid 19 pandemic has an impact on teaching and learning in Higher Education. Research conducted during the pandemic situation aims to find out the picture of selfmanagement in students. A total of 80 people were involved in this study. Sampling is done by convenience or accidental sampling. The method used is descriptive quantitative method. Data retrieved using a measuring instrument in the form of Self-Management scale. The methods of processing and analyzing statistical data are descriptive and inferential. This means that findings such as gender data, aspects of self-management and other additional data are analyzed descriptively and differences in self-management of male and female students are analyzed inferentially with the Man Whitney test in order to describe the profile of self-management comprehensively. The results showed that there were no significant differences in self-management in male and female students. The level of self-management in students is in the medium category. This means that they are capable enough to plan, organize, carry out / direct and control all activities in this pandemic situation. The implication of this research is as preliminary data to see the profile of self-management in students. Keywords: self-management, students, co-19 pandemic